Reflexives and reflexive constructions in Afrikaans - Oosthuizen, Johan (Stellenbosch Papers in Linguistics Plus, 2016)
This article provides a non-formalistic description of the various reflexive pronouns in Afrikaans. In addition to the traditional class of reflexive pronouns, it is shown that possessive pronouns can also be used reflexively. The facts about (obligatory) reflexivity involving these two types of pronoun are illustrated with reference to several types of construction in which they can occur. It is moreover shown that, besides the subject, the reflexive can take as its antecedent an expression functioning as the direct object, indirect object or as a prepositional object. Attention is also given to a number of non-reflexive constructions, that is, constructions containing inherently non-reflexive verbs and prepositions which disallow a coreferential relationship between the pronoun and some other expression in the sentence.